PENGARUH KOMPETENSI DAN KOMPENSASI TERHADAP MOTIVASI KERJA KARYAWAN HOTEL DI KABUPATEN KARO PROVINSI SUMATERA UTARA - Ngatemin .; Wanti Arumwanti (Jurnal Riset AKuntansi dan Bisnis, 2013)
This study aims to find out more about the influence of basic competence and compensation of employees motovasi in Karo, North Sumatra, and to test how much influence competence and compensation of employees motovasi hotel. And the results of this study are expected to serve as a valuable input for authors perform basic tasks lecturer in the activities of Tri Dharma Perguruan Tinggi and become an input for Akademi Pariwisata Medan and become input to management of hotels in North Sumatra, especially those in the Karo district. The method used in this study is a survey method using a data collection tool in the form of a questionnaire with a hotel employee population at Karo. However, because the number of hotels and the employees there are too many samples taken at random (random) and employs 45 people. The data used are primary data and processed using multiple linear regression statistical tests with SPSS tools.The results of this study demonstrate that competence has positive and significant impact on employee motivation hotel with a significant level of 2% at á = 5%. While compensation has positive and significant impact on employee motivation hotel with a significant level of 7.2% at á = 5%.